2021
DOI: 10.1021/acs.jpca.1c01933
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of PNNL Quantitative Infrared Cross-Sections for Isobutane

Abstract: The Pacific Northwest National Laboratory (PNNL) gas-phase database is a compilation of quantitative experimental (5, 25, and 50 °C) infrared spectra of ca. 500 molecules, designed for in situ, standoff or remote sensing of gases and vapors at or near atmospheric pressure. The data are characterized by calibration on both the wavenumber and intensity axes. Recent papers have called into question the PNNL intensity values for isobutane, [2-methylpropane, HC­(CH3)3], suggesting discrepancies of 30–40%. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…and integrated at a 10 cm -1 block interval. We did not observe any dependence of the RE values on the spectral resolution of ACS, which tends to imply a negligible effect of the variation in the linewidth of the ILS on the value of iACS.Johnson et al demonstrated that the iACS of isobutane measured at multiple resolutions between 0.01 and 4.0 cm -1 were in good agreement, thereby implying that resolution dependence did not need to be considered(Johnson et al, 2021). Consequently, RE is indeed an iACS that is weighted by an RF model from 0 to 3000 cm -1 .…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…and integrated at a 10 cm -1 block interval. We did not observe any dependence of the RE values on the spectral resolution of ACS, which tends to imply a negligible effect of the variation in the linewidth of the ILS on the value of iACS.Johnson et al demonstrated that the iACS of isobutane measured at multiple resolutions between 0.01 and 4.0 cm -1 were in good agreement, thereby implying that resolution dependence did not need to be considered(Johnson et al, 2021). Consequently, RE is indeed an iACS that is weighted by an RF model from 0 to 3000 cm -1 .…”
mentioning
confidence: 49%
“…The OPL of MP was calibrated based on HR-FTIR spectroscopy, and its uncertainty was assessed directly. The absorbance measured at high pressures exhibited a different extent of saturation effect according to respective bands, disobeying the linear property of the Beer-Lambert law (Johnson et al, 2021). Therefore, it was critical to use the MP at low partial pressures.…”
Section: Spectroscopic Calibration Methods For the Optical Path Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain low absorption burdens at the nominal OPL of the multipass cell, the gases to be measured were gravimetrically diluted to a designated concentration using an N 2 broadener (the typical gravimetric uncertainty is below 1.5 %). This was also required to ensure the accuracy of the pressure readings for trace levels of the absorbing gas (<0.1 Torr) using pressure gauges, the full scales of which are over 100 Torr (accuracy of 0.05 Torr) with a valid dynamic range of 5 % to 95 % (Johnson et al, 2021). The overall signal-to-noise ratios (S/N) of the absorption spectra were higher than 2000.…”
Section: Instrumental Setupmentioning
confidence: 99%